Documentary imaginary: Production and audience research of The Act of Killing and The Look of Silence. (August 2021) - Hill, Annette
Oppenheimer describes The Act of Killing as a 'documentary about the imagination. We are documenting the ways we imagine ourselves, the ways we know ourselves'. This research analyses the documentary films The Act of Killing (Director Oppenheimer, co-directors Christine Cynn and anonymous 2012) and The Look of Silence (director Oppenheimer 2014), and the documentary imaginary. The research combines normally separate sites of analysis in production and audience studies in order to understand the power of documentary and the spectrum of social stories we inhabit. The article asks: how do the films document and imagine fear and impunity in memories of the genocide, and how do audiences engage with this documentary imaginary? Particular focus is paid towards the endings of the two documentary films and how audiences in this study reflect on the absence of justice for the victims of the genocide. Through the empirical research, we take a journey with the director and his film making process, understanding the lengthy and complex filming for the two documentaries in Indonesia. The films signal Oppenheimer's political and ethical commitment towards victim recognition, the possibility and impossibility of forgiveness, and the challenge of reconciliation between victims and perpetrators. The filmmaker's journey is intertwined with the enactments of the genocide by the perpetrators in their own surreal ways of imagining themselves, and the experience of victims seeking recognition. Audiences become intertwined in these journeys, finding along the way a critically productive space for documentary and the imaginary.